An interictal measurement of cerebral oxygen extraction fraction in MRI-negative refractory epilepsy using quantitative susceptibility mapping - Ebrahimi, Tayyebeh; Tafakhori, Abbas; Hashemi, Hassan; Ali Oghabian, Mohammad (Physica medica, 2021)
•QSM is useful to extract veins through measuring the susceptibility of deoxyhemoglobin.•OEF indicates a parameter of brain metabolism and is a key biomarker of tissue viability.•The increase in OEF in an epileptic brain is due to misery perfusion, representing ischemic tissue. Oxygen extraction fraction (OEF) can be a factor to identify brain tissue’s disability in epileptic patients. This study aimed to assess the OEF’s level measurement in refractory epileptic patients (REPs) using a quantitative susceptibility mapping (QSM) method and to determine whether the OEF parameters change. QSM-OEF maps of 26 REPs and 16 healthy subjects were acquired using 3T MRI with a 64-channel coil. Eighteen regions-of-interest (ROIs) were chosen around the cortex in one appropriate slice of the brain and the mean QSM-OEF for each ROI was obtained. The correlations of QSM-OEF among different clinical characteristics of the disease, as well as between the patients and normal subjects, were also investigated. QSM-OEF was shown to be significantly higher in REPs (44.9 ± 5.8) than that in HS (41.9 ± 6.2) (p < 0.05). Mean QSM-OEF was statistically lower in the ipsilateral side (44.5 ± 6.6) compared to the contralateral side (46.4 ± 6.8) (P < 0.01). QSM-OEF was illustrated to have a strong positive correlation with the attack duration (r = 0.6), and a moderate negative correlation with the attack frequency (r = −0.3). Using an optimized support vector machine algorithm, we could predict the disease in subjects having abnormal OEF values in the brain-selected-ROIs with sensitivity, specificity, AUC, and the precision of 0.96, 1, 0.98, and 1, respectively. The results of this study revealed that QSM-OEF of the REPs’ brain is higher than that of HS, which indicates that QSM-OEF is associated with disease activity.